PELUANG UNTUK MENGURANGI BAHAYA KEBAKARAN - Taufik, Muhammad; Setiawan, Budi I; Prasetyo, Lilik B; Pandjaitan, Nora H; suwarso, suwarso (Jurnal Hidrosfir Indonesia, 2010)
Efforts to anticipate and overcome fire occurrence in wetland wood industries are not effective to reduce fire occurrence in dry season. This paper presents our research in Sebangun Bumi Andalas Wood Industries (SBAWI), South Sumatra that aims to (a) find effective water table depth to reduce fire danger, and (b) propose forest management schemes based on water management to reduce fire danger. We monitored daily rainfall, air temperature, and water table depth for period of 1 April 2009 to 11 May 2010 for data input to our model. Fire danger rating was assessed using KBDI model that have been modified to meet local condition of SBAWI, South Sumatra. The results showed that KBDI reached extreme level in August and September 2009 when rainfall was low. Using an analysis of time intensity curve (TI curve) of KBDI, we obtained KBDI onset rate was 12/day. Critical water table depth that is able to reduce KBDI value was 0.66m. The more water table depth than this value, the more KBDI value was. The onset rate was used as basis for water management option to maintain water table depth less than the critical value. Several water management options were described in this paper based on fire danger level and season.